Validation of reference genes in pansy for accurate transcript normalization during its flowering stages - Zeng, Yuan; Li, Jing; Gong, Sheng; Zhang, Ke; Sun, Haiyan; Zhu, Guopeng; Song, Xiqiang; Wang, Jian (The Indian Journal of Genetics and Plant Breeding, 2016)
Quantitative real-time PCR (qRT-PCR) is a perfect method for rapid and accurate quantification of gene expression in different organs or at different development stages in plants. Suitable reference genes are important in this method. In order to obtain more accurate genes expression data in pansy (Viola Ã— wittrockiana Gams.) flower, the expression stability of four housekeeping genes, Î²Î² Î²Î² Î²-actin (ACT), glyceraldehyde-3-phosphate dehydrogenase (GAPDH), tubulin (TUB) and 18S ribosomal proteins (18S) at seven different floral development stages in pansy were studied in this experiment. The results showed that TUB and 18S genes were the top two stable genes. Additionally, the expression pattern of VwbHLH1 gene was studied with the two most stable reference genesTUB and 18S, and the worst gene GAPDH respectively. The gene expression data were very different when various reference genes were applied. The present study proved that selection of reference genes was definitely important to obtain precise experimental data in qRT-PCR even for the same organ but at different development stages. This study would provide guidelines to obtain more accurate gene expression results for future molecular mechanism study in pansy.